Ecogenotoxicology in earthworms: A review. Issue 2 (1st April 2014) - Vasseur, Paule; Bonnard, Marc
Abstract: Pollutant dynamics and bioavailability greatly differ in soil and aquatic systems. Therefore, specific approaches and models are needed to assess the impact of soil contamination to terrestrial ecosystems. Earthworms among other soil invertebrates have received more attention because of their ecological importance. They represent a dominant part of the soil biomass and are soil engineers regulating important soil processes, notably fertilization. The release in soils of pollutants known for their persistence and/or their toxicity is a concern. Exposure of terrestrial species to pollutants that may alter genomic function has become an increasing topic of research in the last decade. Indeed, genome disturbances due to genetic and epigenetic mechanisms may impair growth, as well as reproduction and population dynamics in the long term. Despite their importance in gene expression, epigenetic mechanisms are not yet understood in soil invertebrates. Until now, pollutant-induced changes in genome expression in natural biota are still being studied through structural alteration of DNA. The first biomarker relating to genotoxicant exposure in earthworms from multi-contaminated soils reported is DNA adducts measurements. It has been replaced by DNA breakage measured by the Comet assay, now more commonly used. Functional genomic changes are now being explored owing to molecular "omic" technologies. Approaches, objectives and results are overviewed herein. The focus is on studies dealing with genotoxicity and populational effects established from environmentally-relevant experiments and in situ studies.